Feline Leukemia Virus (FeLV) in Cats Domestic: A Case Study - Fatra, Ilhami Maulia; Cadiwirya, Pradhana Kurniawan; Prasetyo, Dodik; Noviatri, Aldila; Kristanto, Dwi (IPB University, 2025)
Feline Leukemia Virus (FeLV) is one of the major causes of death in cats. A 4-year-old domestic cat weighing 2 kg presented with decreased appetite, weakness, sneezing, and nasal discharge. Physical examination revealed gingivitis accompanied by ulcers in the mouth and pale mucous membranes. Further diagnostic tests included hematology examination, blood chemistry examination, and the FeLV test kit. The results of hematology and blood chemistry examinations reported that the animal had leukocytosis, neutrophilia, thrombocytopenia, hypochromic macrocytic anemia, hyperproteinemia, hyperglobulinemia, decreased A/G ratio, hyperamylasemia, hyperbilirubinemia, and azotemia. Rapid test (kit) examination showed a positive result for FeLV. Based on the diagnostic results, the initial diagnosis was suspected Feline leukemia virus (FeLV) with an infausta prognosis. The treatment included antibiotics Amoxicillin at 18 mg/kgBW, Diphenhydramine HCl 1 mg/kgBW, Ornipural® 0.2 ml/kgBW, Kenalog® 1 mg/kgBW, Hematovit® dose 0.4 ml/kgBW, and supplements in the form of Vitamin C 0.5 ml/day and Fufang® 1 ml/kgBW. Despite the treatment, the cat’s condition did not improve and it succumbed on the sixth day of treatment.